P001 A Qualitative Study to Compare Food-Insecure College Students’ Eating Behaviors With and Without Access to a Campus Food Pantry - Mooney, Grace; Drake, Teresa; Vollmer, Rachel L. (Journal of nutrition education and behavior, 2022)
Food-insecure college students have an increased likelihood of developing disordered eating behaviors, possibly due to coping behaviors including restriction when food is scarce and bingeing when food is abundant. While more and more universities are adding on-campus food pantries, it is unclear how access to on-campus food pantries impacts eating behaviors and food insecurity. To explore how the cycle of food abundance and scarcity impacts food-insecure college students’ eating behaviors and how access to a campus food pantry impacts this cycle. Food-insecure, undergraduate students (n = 40) from institutions around Illinois with food pantries (n = 20) and without food pantries (n = 20) who met inclusion criteria completed one-on-one semi-structured interviews via Zoom. Interviews were audio-recorded and transcribed verbatim. Investigators performed content analysis to identify and compare themes among participants with and without access to a campus food pantry. Students with and without access to a campus food pantry discussed similar experiences, including experiencing periods of food abundance and scarcity, and using a variety of food-related behaviors to cope with their food situation. Some students attending institutions with an on-campus food pantry were unaware that a pantry existed. Students from both types of institutions reported that although they did not use one, an on-campus pantry has the potential to increase food availability and improve eating habits; however, regardless if a pantry was on campus, students reported that shame and embarrassment would prevent them from using university resources. Food-insecure college students may exhibit disordered eating behaviors, including restriction and binge eating, to cope with their food situation. Furthermore, the existence of a campus food pantry alone is insufficient for addressing college food insecurity and the corresponding disordered eating behaviors. Bradley University C. C. Wheeler Institute